A prática reflexivo-colaborativa na formação de três professoras de inglês - PEREIRA, Jane Beatriz Vilarinho (2010)
This collaborative research (MAGALHÃES, 2002) investigates the role of critical reflection (SMYTH, 1991) in the participant s development and in the reconstructing of their ctions. The research was conducted with a group of three English teachers, one being the researcher, in a language center in the city of Goiânia. From August 2008 to December 2009, the group had regular meetings to discuss theoretical texts and analyse their lessons which had been recorded. The analysis focused on the participants concepts of language and teaching; on the types of reflection; and on the change proposals for their actions. It was also examined whether these changes were motivated by the readings or by the collaboration among the participants during the reflective sessions. Considering the main concepts in which this research is based on, we point out: the critical reflection as an important tool in the development of teachers autonomy, awareness and education; the collaborative work as an element that can foster the development of critical reflection, and the acknowledgement of teachers knowledge supported by their experience as well as the investigation of their own practice. The results revealed that different concepts of language and teaching can be found not only in the discussions but also in the teachers practice. This fact is in accordance with a view of language as a set of elements structure, culture, ideology that are integrated and are not mutually exclusive (TUDOR, 2001). In relation to the development of reflection, it achieved a critical level, which can be perceived by the approach of different topics related to language teaching such as: the teaching of the language for specific purposes as a way of avoiding colonization; the role of the teacher, the student and the negotiation of power in the classroom; and the teacher as a instructor or educator. These collaborative reflections gave rise to some proposals for change which were presented to the other teachers who had not participated in the research and to the coordinator of the language center. Some of them have already been implemented. To sum up, we believe this study has contributed to the development of the collaborative work and the process of critical reflection as well as to their acknowledgement as tools to promote teacher education and change realities.